(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The paper describes the influence of electric current on the porosity of concrete samples after electrically accelerated tests and other electrokinetic treatments. Three different concrete mixtures consisting of CEM I 42.5R, CEM II / A-M(S-LL) 42.5R, and CEM I 42.5R with 10 % replacement of cement by microsilica were examined. Direct current (DC) test was performed on fully saturated samples. The samples were loaded with a constant voltage of 20 V for 24 hours in chambers filled with NaOH solution. The changes in porosity were examined using mercury intrusion porosimetry (MIP), scanning electron microscopy (SEM), and open porosity (OP). The results of open porosity indicate an increase in porosity for all mixtures measurements of ∼0.6 %–2 % for treated samples. The MIP showed increase of volume of pores with radius smaller than 0.01 μm after DC test. According to X-ray diffraction (XRD) and Thermogravimetric analysis (TGA) there was ∼2 % less calcite after DC test.